The Creative Buddhist Tourism Management of Temples in Bangkok Thailand - boonkrongsupya, jirakitiya; Phra Sutheerattanabundit; Raksachom, Maechee Kritsana (Mahachula Academic Journal, 2025)
This research aims to study 1) to study temple tourism in Bangkok and 2) to develop and promote temple tourism activities in Bangkok. and 3) to propose a creative Buddhist tourism management model for temples in Bangkok. This is a mixed research method, consisting of documentary research and qualitative research. It is a research process that aims to develop activities and creative media for Buddhist tourism in temples in Bangkok. The target group is 4 temples that are important sources of learning about Buddhism and culture at a high level at the national level. From the study (1) The process of managing temple tourism in Bangkok found that the management process starts from organizing temple activities, temple resources, and temple activity support. It is considered a process of managing tourism according to beliefs and culture.Including Buddhist art depending on the context of the temple’s tourism activities and tourists visiting the temple because there are more people visiting and learning in the temple. In the past, temples mainly served to spread Buddhism and organize activities on important Buddhist days. Then society began to change until it became a modern learning society. Tourists began to visit the ancient art of the temple which is a tourist attraction. The physical environment must be arranged.Environment: Improve the landscape and clear the temple walls to promote tourism and learning activities. (2) Buddhist tourism for developing the mind and wisdom in the dimensions of practicing the principles of Buddhism at temples in Bangkok found that There are tourism factors, namely the beauty of Buddhist art, culture, traditions and Buddhist activities that support learning and practicing according to Buddhist principles that arise from the wisdom of Buddha statue making. The creation of architecture and painting has the potential to be developed into a creative tourism learning resource. (3) The creative Buddhist tourism management model of temples in Bangkok found that the components of tourism that emphasize on strengthening the relationship with the management of temple activities There is a management process in the form of organizing temple tourism activities continuously while tourists receive convenience. Learning and participating in cultural and Buddhist activities consists of four elements: groups of people, temples and places, tourism management, and tourism benefits.